Recursos da informação e os cursos de mestrado da área biomédica na Universidade Federal Fluminense - Garcia, Márcia Japor de Oliveira (1978)
The aims of post-graduate courses at Universidade Federal Fluminense are examined, and a survey was done, involving 70 teachers and 112 students of the biomedical area, dealing with aspects related do informtion resources needs and use, There is some problem concerning interaction library-courses, and the communicationlibrary-users. The use of sectorial libraries mus be more effective. In spite ogthe assistance for research and keeping users up to date were considered unsatisfactory, titles of serials and reference material most used constitute part of the collection. In the information access, formal channels are more effective, being abstracts and index considerably employed. The course on Veterinary uses thegreater number of refernce titles. Language barrier exists. Interlibrary loan was stimulated and its dissemination and evalution, as well as the dissemination of MEDLINE were suggested. To study and research, respondents considered the necessity of an exclusive palece into the lbrary. The suggestions were formulated with the purpose to provide means to a better interaction library-courses and to attain that courses objectives.